Developing Undergraduate Student Teachers’ Competence in Integrative STEM Teaching - Yip, Wing Yan Valerie (Frontiers in Education, 2020)
Developing students’ literacy in Science, Technology, Engineering, and Mathematics (STEM) has been a major education issue since the 1990s. STEM education aims to support students to make informed decisions on social issues and become global citizens. In contrast with the interdisciplinary nature of STEM, initial teacher training usually focuses on teaching discrete subject disciplines. Novice teachers may also lack the relevant training in design and engineering to foster the practices in the classrooms. This article reports an initiative of preparing 25 pre-service teachers for integrative STEM teaching. The 24-h course combined the learning of design concepts and teaching inquiry within teaching the science content. Lesson activities of STEM classrooms engaged the novice teachers as “students”; and then they were prompted to reflect metacognitively on how they could support the “students” as teachers. Results from the questionnaires and focus group interviews indicated the importance of engaging the novices both as learners and future teachers of STEM education.